2022
DOI: 10.1186/s12889-021-12434-9
|View full text |Cite
|
Sign up to set email alerts
|

Food access, mobility, and transportation: a survey and key informant interviews of users of non-profit food hubs in the City of Vancouver before and during the COVID-19 crisis

Abstract: Background In the City of Vancouver, Canada, non-profit food hubs such as food banks, neighbourhood houses, community centres, and soup kitchens serve communities that face food insecurity. Food that is available yet inaccessible cannot ensure urban food security. This study seeks to highlight food access challenges, especially in terms of mobility and transportation, faced by users of non-profit food hubs in the City of Vancouver before and during the COVID-19 crisis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Furthermore, we found that the majority of food hubs surveyed intentionally selected a location that is easily accessible to low-income households. This supports previous findings in the literature [ 56 , 57 , 58 ] and suggests that our previous analysis may not have sufficiently picked up on the nuances of the relative distance to low-income households. The accessibility indicator received a higher score of 70% which is significantly higher than the 53% score in our previous study.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Furthermore, we found that the majority of food hubs surveyed intentionally selected a location that is easily accessible to low-income households. This supports previous findings in the literature [ 56 , 57 , 58 ] and suggests that our previous analysis may not have sufficiently picked up on the nuances of the relative distance to low-income households. The accessibility indicator received a higher score of 70% which is significantly higher than the 53% score in our previous study.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…This included the challenges of managing the emotional stressors and vulnerabilities among staff, volunteers and clients while also overseeing complex and evolving changes to service delivery, safety protocols amid insufficient resources and supports to meet the needs of clients [ 2 ]. Other challenges to accessing and running food banks in the context of the pandemic have also been reported in Ontario [ 56 ], British Columbia [ 57 ] and by Food Banks Canada [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our nationally representative data are similar to those from other countries where large unmet gaps in food needs are concentrated among people who are marginalized and/or living in poverty. Inadequate social safety nets have been documented in several other high-income countries, with growing evidence that despite the proliferation and entrenchment of food banks as a primary response to unmet food need, charity-based food approaches have failed to address the growing challenges of food insecurity before or during the COVID-19 pandemic [ 30 , 31 , 33 , 57 – 59 ]. For example, Dekkinga et al describe how food banks have become an entrenched part of the Dutch food system, while additional approaches are needed to address the root causes of food insecurity, inequality, and poverty [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Mid-Ohio Food Collective, Grove City, Ohio. 4 College of Public Health, The Ohio State University, Columbus, Ohio.…”
Section: Author Informationmentioning
confidence: 99%